Sustainable Organocatalyzed Enantioselective Catalytic Michael Additions in Betaine-Derived Deep Eutectic Solvents - Fonseca, Daniela P.; Amorim, Ana C.; Carreiro, Elisabete P.; Ramalho, João P. Prates; Hermann, Gesine J.; Federsel, Hans-Jürgen; Duarte, Ana Rita C.; Burke, Anthony J. (SynOpen, 2023)
The organocatalyst cinchonidine-squaramide was immobilized within three different deep eutectic solvents (DESs): betaine:d-sorbitol:water, betaine: d-xylitol:water, and betaine:d-mannitol:water and evaluated in a well-known asymmetric Michael addition. These reactions provided excellent yields (up to 99%) and enantioselectivities (up to 98%) using only 1 mol% of organocatalyst. It was also possible to achieve 9 cycles in reactions with DES (betaine:d-sorbitol:water), proving the high recyclability of this system. In the reactions realized with only 0.5 mol% of organocatalyst, it was possible to achieve 5 cycles, and the products were obtained with high yields (up to 95%) and excellent enantioselectivities (up to 94%), using DES (betaine:d-sorbitol:water).
Keywords: cinchonidine-squaramide; betaine; deep eutectic solvent (DES); immobilization; organocatalysis